Effectiveness of Same-Day Human Ear Wax Removal as an Office Procedure and Factors Associated with its Successful Removal - Singh, Madan Mohan; Pandey, Bhuwan Raj; Pandit, Shiva Bhushan (Journal of Lumbini Medical College, 2017)
Introduction: There are various methods of ear wax extraction and there are no specific guidelines on this subject. Many times we ask patients to instil some wax softening product for a few days and revisit for wax removal. These revisits result in increased cost, discomfort and loss of time. We conducted this study to determine the effectiveness of same-day ear wax removal as an office procedure with one or more techniques. Our secondary objective was to find the association between various factors and successful wax removal. Methods: During the study period, all patients with ear wax managed by a single ENT surgeon were included. History and examination were done and findings noted. One or more methods including probe, forceps, hooks, curette, suction, wax softening with wax softening agents, syringing were applied for wax removal. Complete wax removal was noted as success. Results: There were a total of 63 cases of ear wax among 34 participants. Wax was successfully removed in 52 (82.5%) cases in the same day. Presence of ear ache, narrow canal, complete obstruction and hard dry wax were adversely associated with successful wax removal. Presence of ear fullness, ear discharge, or use of ear drops in home was not significantly associated with successful ear wax removal. Conclusion: We were able to extract wax from a large proportion of patients on the same day of visit, thereby reducing their cost of revisit, however there were 17.5% of cases who could not be treated successfully on the same day.